Detailed Evidence for an Unparalleled Interaction Mode between Calmodulin and Orai Proteins. Issue 49 (6th November 2017) - Traxler, Lukas; Rathner, Petr; Fahrner, Marc; Stadlbauer, Michael; Faschinger, Felix; Charnavets, Tatsiana; Müller, Norbert; Romanin, Christoph; Hinterdorfer, Peter; Gruber, Hermann J.
Abstract: Calmodulin (CaM) binds most of its targets by wrapping around an amphipathic α‐helix. The N‐terminus of Orai proteins contains a conserved CaM‐binding segment but the binding mechanism has been only partially characterized. Here, microscale thermophoresis (MST), surface plasmon resonance (SPR), and atomic force microscopy (AFM) were employed to study the binding equilibria, the kinetics, and the single‐molecule interaction forces involved in the binding of CaM to the conserved helical segments of Orai1 and Orai3. The results consistently indicated stepwise binding of two separate target peptides to the two lobes of CaM. An unparalleled high affinity was found when two Orai peptides were dimerized or immobilized at high lateral density, thereby mimicking the close proximity of the N‐termini in native Orai oligomers. The analogous experiments with smooth muscle myosin light chain kinase (smMLCK) showed only the expected 1:1 binding, confirming the validity of our methods. Abstract : The mechanism by which calmodulin interacts with a conserved segment of different Orai proteins was characterized by a combination of equilibrium, kinetic, and single‐molecule force measurements. The results consistently supported the two‐step binding of one calmodulin molecule to two Orai segments, with distinctly different affinities, kinetics, and interaction forces.